Rekayasa Penguraian Kemacetan Lalu Lintas Pada Simpang Empat (Studi Kasus: Jalan Andi Mappaodang Dan Jalan Andi Mangerangi Makassar) - Febrian , Ivan Othinel; Stevy; Mursalim (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Atma Jaya Makassar, 2025)
Intersections are a very crucial part of the highway because most of the efficiency, safety, speed, operational costs and traffic capacity depend on the intersection planning. Good intersection planning results in smooth traffic. This study aims to determine the queue length at the intersection of Andi Mangerangi Street and Andi Mappodang Street in Makassar, as well as to analyze the queue length at this intersection. The research models two alternative engineering solutions by altering the geometric conditions of the intersection and adding traffic signs. The software used to assist in the study is PTV Vissim 2024 and Measure Distance, which helps measure the queue length that occurs. The results of the study from the two planning models show that the initial planning model, with the existing geometric conditions, resulted in the following queue lengths: Andi Mangerangi Street (West) had a queue length of 228m, Andi Mangerangi Street (East) had 119m, Andi Mappaodang Street (North) had 166m, and Andi Mappaodang Street (South) had 196m. After conducting several trials, it was concluded that the chosen alternative is alternative 2, which involves changing the geometric conditions of the road and adding traffic signs. This alternative resulted in the following queue lengths: Andi Mangerangi Street (West) had 182m, Andi Mangerangi Street (East) had 98m, Andi Mappaodang Street (North) had 105m, and Andi Mappaodang Street (South) had 163m.